1989
DOI: 10.1104/pp.91.3.848
|View full text |Cite
|
Sign up to set email alerts
|

Whole Leaf Carbon Exchange Characteristics of Phosphate Deficient Soybeans (Glycine max L.)

Abstract: Walker and Sivak (29) reviewed a set of plant attributes that respond to low Pi nutrition, which they term "the syndrome of Pi deficiency." The responses to low Pi include increased oscillatory behavior in A3 at lower light levels,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
56
1
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 26 publications
(33 reference statements)
10
56
1
3
Order By: Relevance
“…Such an effect has been reported for spinach (Brooks, 1986), soybean (Lauer et al, 1989), and loblolly pine (Tissue et al, 1993 (Woodrow et al, 1983;Sicher and Kremer, 1988;. Changes in activities of these enzymes could regulate the activity of Rubisco to obtain an equilibrium of the photosynthetic carbon reduction cycle.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Such an effect has been reported for spinach (Brooks, 1986), soybean (Lauer et al, 1989), and loblolly pine (Tissue et al, 1993 (Woodrow et al, 1983;Sicher and Kremer, 1988;. Changes in activities of these enzymes could regulate the activity of Rubisco to obtain an equilibrium of the photosynthetic carbon reduction cycle.…”
mentioning
confidence: 67%
“…In contrast, the effects of phosphorus deficiency on photosynthesis in annual plants has a more extensive coverage. It is widely recognized that a reduction in nutrient availability affects the dark reactions of photosynthesis and decreases carboxylation efficiency (Brooks, 1986;Lauer et al, 1989). In addition, it has been reported that phosphorus deficiency also decreases the quantum efficiency Lawlor, 1991, 1993;Lewis et al, 1994), but has no effect on the maximal rate of electron transport (Lewis et al, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in photosynthetic efficiency under P stress have been reported in various crops such as barley and spinach (Foyer and Spencer, 1986), soybean (Lauer et al, 1989), maize (Usuda, 1995), wheat (Rodríguez et al, 1998), pigeon pea (Fujita et al, 2004) and rice (Wissuwa et al, 2005).…”
Section: P Limitation Effects On Plantsmentioning
confidence: 99%
“…In healthy mature leaves, total protein concentrations were highest at 40 mmol Pi plant 21 d 21 . Such large increases in leaf protein concentration with increasing Pi supply have not been reported in other plants, where changes in protein concentrations are relatively small (Lauer et al, 1989;Rao and Terry, 1989). It was also noteworthy that in H. prostrata, increased Pi supply did not lead to an increase in leaf fresh weight (Fig.…”
Section: Leaf Pi Accumulation and Inhibition Of Its Conversion Into Omentioning
confidence: 60%